2021
DOI: 10.3390/risks9040074
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin and Altcoins Price Dependency: Resilience and Portfolio Allocation in COVID-19 Outbreak

Abstract: The main aim of this article is to examine the inter-relationships among the top cryptocurrencies on the crypto stock market in the presence and absence of the COVID-19 pandemic. The nine chosen cryptocurrencies are Bitcoin, Ethereum, Ripple, Litecoin, Eos, BitcoinCash, Binance, Stellar, and Tron and their daily closing price data are captured from coinmarketcap over the period from 13 September 2017 to 21 September 2020. All of the cryptocurrencies are integrated of order 1 i.e., I(1). There is strong evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The model applied was VAR and ARMA-GARCH. Ahmet Faruk Aysan, Asad Ul Islam Khan, and Humeyra Topuz investigated the effect of 9 cryptocurrencies during the pandemic [9]. They used different models to obtain the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The model applied was VAR and ARMA-GARCH. Ahmet Faruk Aysan, Asad Ul Islam Khan, and Humeyra Topuz investigated the effect of 9 cryptocurrencies during the pandemic [9]. They used different models to obtain the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…On of the early research that explores the connections between the leading cryptocurrencies on the cryptocurrency markets in cases with and without the Covid-19 pandemic is Aysan et al (2021). The nine cryptocurrencies that have been selected in this paper are Bitcoin, Ethereum, Ripple, Litecoin, Eos, Bitco-inCash, Binance, Stellar, and Tron.…”
Section: General Aspect Of Crypto Market During Covidmentioning
confidence: 99%
“…At the same time, the behaviour of Bitcoin on fiat currencies (e.g., USD, Euro) is relative, but the asymmetric relationship with Altcoins is unexplored [23] . The market movement showed that cryptocurrencies are significantly more unpredictably and vary much widespread than fiat currencies [1,24,25] . Since July 2017 crypto market witnessed a boom in ICO (Initial Coin Offerings), and this paradigm decreased the dominance of Bitcoin from 85% to below 45% [26] .…”
Section: Review Of Literaturementioning
confidence: 99%
“…In later stages, other digital currencies are introduced to the market as Alternative Coins such as Lite coin, Ethereum, Doge, etc., and it is shortly named Altcoins. The Market Price of Bitcoin increased tremendously (±12000%) in the last five years, and its total capitalisation reached $660Billion [1] . The innovative features, transparency, and simplicity led to increasing popularity among traders.…”
Section: Introductionmentioning
confidence: 99%